Patterns of mutation within an emerging endemic lineage of HEV‐3a. Issue 1 (14th November 2018) - Zhu, Yuan O.; Aw, Pauline; Aung, Myo Myint; Lee, Hong Kai; Hibberd, Martin; Lee, Guan Huei
Summary: The hepatitis E virus can cause chronic infections in immuno‐suppressed patients, and cases have been on the rise globally. Viral mutations during such infections are difficult to characterize. We deep‐sequenced viral populations from 15 immunocompromised patients with chronic HEV to identify the viral lineage and describe viral mutational hotspots within and across patients. A total of 21 viral RNA samples were collected between 2012 and 2017 from a single hospital in Singapore. Sequences covering a total of 3894 bp of the HEV genome were obtained. Phylogenetic analyses identified all sequences as belonging to the HEV‐3a sub‐clade and clearly indicate a unique local lineage. Deep sequencing reveals variable viral population complexity during infections. Comparisons of viral samples from the same patients spaced 2‐19 months apart revealed rapid nucleotide replacements in the dominant viral sequence in both ribavirin treated and treatment‐naive patients. Mutational hotspots were identified within ORF3 and the PCP/HVR domain of ORF1.